2001
DOI: 10.1542/peds.107.2.e19
|View full text |Cite
|
Sign up to set email alerts
|

Abused Boys, Battered Mothers, and Male Involvement in Teen Pregnancy

Abstract: ABSTRACT. Background. The relationship between boyhood exposure to physical abuse, sexual abuse, or to a battered mother and subsequent risk of impregnating a teenage girl has not previously been examined.Methods. In a retrospective cohort study set in a primary care clinic for adult members of a large health maintenance organization, questionnaire responses from 4127 men were analyzed. Respondents provided the age of the youngest female whom they had impregnated, their own ages at the time, and information re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0
6

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 66 publications
(53 reference statements)
1
67
0
6
Order By: Relevance
“…[13][14][15][16][17][18][19][20][21] These and related reports demonstrate strong and graded associations between cumulative exposure to categories of ACE and many unfavorable reproductive health outcomes, including early onset of sexual activity, adolescent pregnancy, sexually transmitted diseases, increased risk of HIV infection, violence perpetration, unintended pregnancy in adulthood, and fetal death. 13,14,16,22,23 Data collected in the second wave of the study also included measures of family strengths, which should protect against these unfavorable outcomes.…”
mentioning
confidence: 59%
“…[13][14][15][16][17][18][19][20][21] These and related reports demonstrate strong and graded associations between cumulative exposure to categories of ACE and many unfavorable reproductive health outcomes, including early onset of sexual activity, adolescent pregnancy, sexually transmitted diseases, increased risk of HIV infection, violence perpetration, unintended pregnancy in adulthood, and fetal death. 13,14,16,22,23 Data collected in the second wave of the study also included measures of family strengths, which should protect against these unfavorable outcomes.…”
mentioning
confidence: 59%
“…Previous publications from the ACE Study have demonstrated strong relationships of various interrelated adverse childhood experiences to multiple risk factors for the leading causes of death in the United States, 25 and to priority health and social problems, such as smoking, 26 sexually transmitted diseases, 27 unintended pregnancies, 28 male involvement in teen pregnancy, 29 alcohol and illicit drug problems, 30 -32 liver disease, 33 and suicide attempts.…”
Section: Methodsmentioning
confidence: 99%
“…Les jeunes pères ont plus souvent que les autres jeunes connu des milieux familiaux difficiles (Furstenberg et Weiss, 2000). Beaucoup plus fréquemment que la population de jeunes hommes sans enfant du même groupe d'âge, ils ont subi des abus physiques ou sexuels ou ont été témoins de violence conjugale (Anda, Felitti, Chapman et al, 2001), ont souffert de l'absence de leur père, de son désengagement ou de rapports conflictuels avec celui-ci (Allen et Doherty, 1996;Tuffin, Rouch et Frewin, 2010).…”
Section: Recension Des éCritsunclassified